The Role of the Tulungagung Police Research Unit to Guarantee Kamtibmas in Handling Social Conflict Between Silat Colleges - Sandy, Gabriel (Advances in Police Science Research Journal, 2024)
Social conflicts between silat teachers still occur frequently and disturb the community. Enforcement The laws implemented by the National Police are still implemented with the aim of providing a deterrent effect to cases of perpetrators of criminal acts related to conflicts between martial arts schools. that problem raised can be formulated as follows: 1) what are the factors that cause conflict social between martial arts schools? 2) What is the role of the police unit in resolving related problems? with conflicts between silat schools, thereby creating safe and peaceful conditions? This research uses a qualitative approach. Researchers use theories and concepts to discuss the problems in this final assignment. The theory used by researchers is theory management, role theory, SWOT theory, and the concepts used are the concept of law enforcement and the concept of security and social order. The results of the research show that the Tulungagung Police Criminal Investigation Unit has implement law enforcement to provide a deterrent effect to perpetrators of related criminal acts with social conflict between martial arts schools. Implementation of law enforcement by the Police Criminal Investigation Unit Tulungagung in an effort to reduce criminal cases related to social conflict between The martial arts school in the Tulungagung Police jurisdiction has been implemented in accordance with the appeal from East Java Regional Police Chief, that every problem related to the martial arts school must be resolved with law enforcement.